Assessing adaptation options for climate change: A guide for coastal communities in the Coral Triangle of the Pacific 6. Landscape Function Analysis - WorldFish (2013)
Assessing options for adapting to climate change is an important part of building resilient fishing and farming communities. This brochure is part of a series that collectively detail how a community-based assessment of climate change was used in partnership with coastal communities and provincial and national-level stakeholders in Timor-Leste and Solomon Islands. The assessment contains four distinct, but related, steps (Fig 1) focused on supporting community-level decision-making for adaptation through a series of participatory action research activities. Each brochure in this series details a specific activity in the four-step assessment. This series of eight brochures is primarily aimed for use where resources are limited or where it is more appropriate to use a rapid, qualitative and non-data intensive method of assessment. Community leaders, local NGOs and regional and national-level government representatives in developing countries may find this series useful. In this brochure we provide details of an activity relating to the ‘Evaluation of options’ step of the assessment, namely Landscape Function Analysis (LFA). This activity was conducted with community members to measure the ecological function of different types of home garden production systems (Figs 2-5). More specifically, the following questions were posed: • How well do different home garden types function ecologically (using soil condition as an indicator)? • Which parts of a home garden (e.g., leaf litter, crop residue) provide the most benefits in terms of ecological functioning? • How might these functions change due to the introduction of adaptation actions? • How can communities improve ecological function of agricultural land to enhance resilience to climate change? Fig 1: The four steps taken by community, local NGOs and regional and national government representatives in developing a plan to respond to climate change. Each step addresses specific questions likely to be asked by community members needing to adapt. Scoping What are key natural resource issues and drivers of change impacting the resilience of fishers’ and farmers’ livelihoods? Research method: Climate analysis Identifying options What are likely impacts of a changing climate and what adaptations might be useful? Research method: Impact and adaptation assessment workshop What does a desirable future farming/fishing livelihood look like? Research method: Community visioning activity Evaluation